A Study on Cost Benefit Analysis of Tur (Red Gram) With Reference To Dry Land in Solapur District (International Journal of Food and Nutritional Sciences, 2022)
The present study was carried out in all the tehsils in Solapur district to study cost ofcultivation, prices and profitability of Tur (Red Gram) production. The study was based on theprimary data of 50 Tur (Red Gram) cultivators for the year 2020-21. The average per acre cost ofcultivation of Tur (Red Gram) was estimated to Rs. 18889 and per quintal cost was estimated to Rs.5373.